Physicochemical Characterization and Comparative Analysis of Ribulose 1,5 Biphosphate Carboxylase-Oxygenase Like Proteins (RLP) from Halophilic Chromohalobacter salexigens BKL 5 and Non-Halophilic Counterparts Using in Silico Approaches - Irwan Sudarmanto; Wayan Tunas Artama; Muhammad Saifur Rohman (Jurnal Kimia Sains dan Aplikasi, 2024)
This study is intended to analyze and compare halophilic RuBisCo-like proteins (RLP) with non-halophilic homologs using computational analysis approaches. The data used were protein sequences from NCBI and protein sequences from clonned and expressed RuBisCo-like proteins Chromohalobacter salexigens BKL 5 from our previous study. The analysis was in the form of Principal Component Analysis (PCA) and Partial Least Square (PLS). The tools used were Origin Lab Full Version 2019 and Metaboanalyst 5.0. The parameters tested were isoelectric point (pI), negative charge (acidic amino acids), aliphatic index, and GRAVY index using the ProtParam tool from Expasy. Calculations analysis showed that the amino acid residues in halophilic RuBisCo-like proteins that differ significantly from their homologs were glutamic acid and alanine, while the variables that could be observed as differentiating were negative charge and aliphatic index. Analysis shows that some parameters obtained from the program can be used as discriminants to differentiate halophilic and non-halophilic RuBisCo-like proteins.